2023
DOI: 10.1002/eng2.12613
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of computed tomography equipment using the q‐Weibull distribution

Abstract: Inspired by the successful application of the q‐Weibull distribution in other research fields, we took the lead to use it in the field of medical devices in this work. The parameter estimation of the q‐Weibull distribution was performed using the probability plot method. The CT failure data from Nanfang Hospital in Guangzhou, China, were used to study the reliability of CT equipment at two levels: the CT system and its seven main components. In terms of evaluation accuracy, the mean squared error, Akaike's inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…However, above the visual analysis of the failure rate function, the shape parameter, β, is decisive in the analysis and enables the identification of failure type. Depending on the value of β, the failure rate, λ, evolves differently and can be associated with one of the phases of the bathtub curve [ 50 ], typical for engineering systems [ 51 ]: If β < 1, the failure rate is decreasing, typical of the “burn-in” period. This kind of failure rate indicates an “early failure” and is typically associated with systems with manufacturing defects; If β = 1, the failure rate is constant, typical of the “useful life” period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, above the visual analysis of the failure rate function, the shape parameter, β, is decisive in the analysis and enables the identification of failure type. Depending on the value of β, the failure rate, λ, evolves differently and can be associated with one of the phases of the bathtub curve [ 50 ], typical for engineering systems [ 51 ]: If β < 1, the failure rate is decreasing, typical of the “burn-in” period. This kind of failure rate indicates an “early failure” and is typically associated with systems with manufacturing defects; If β = 1, the failure rate is constant, typical of the “useful life” period.…”
Section: Methodsmentioning
confidence: 99%
“…However, above the visual analysis of the failure rate function, the shape parameter, β, is decisive in the analysis and enables the identification of failure type. Depending on the value of β, the failure rate, λ, evolves differently and can be associated with one of the phases of the bathtub curve [50], typical for engineering systems [51]:…”
Section: Tracking Duration Analysismentioning
confidence: 99%
“…Moreover, [6] illustrated the effectiveness of the q-Weibull distribution in analyzing the reliability of computed tomography (CT) equipment failure data. The authors demonstrated that the q-Weibull distribution could effectively describe the entire bathtub curve, which is a graphical representation of the failure rate over time.…”
Section: Introductionmentioning
confidence: 99%